From Majelis Taklim to Majelis Selawat: Tracing the Cultural Transformation of Islamic Preaching in Java - Afif Kholidin; Supriyadi Supriyadi; Ma'mun Mu'min; Ida Nur Lailatul Kodriyah (Indonesian Journal of Islamic Religion and Culture, 2024)
Cultural evolution has occurred in various aspects of community life, including religious practices. In Indonesia, religious study groups (majlīs taʻlīm) and prayer groups (majlīs ṣalāwāt) are two forms of religious activities that play an important role in the spiritual development of Muslims. However, recently, prayer groups (majlīs ṣalāwāt) have become more popular than religious study groups (majlīs taʻlīm). This study aims to examine the cultural evolution in the religious practices of the Muslim community in Indonesia, focusing particularly on the transition from religious study groups to prayer groups. The study was conducted using a literature review method, collecting data from various relevant sources. The results show that this shift is influenced by several factors, including the appeal and interactivity of prayer group activities, their emotional impact, ease of understanding, and the strengthening of the communities involved. Furthermore, technological advancements and new media have accelerated the spread and popularity of prayer groups, particularly among the younger generation. The impact of this evolution includes changes in the function and tone of religious studies, the integration of music into spiritual activities, and the emergence of new forms of cultural expression that blend tradition and modernity. This study provides insight into how social and cultural changes shape religious practices and the spiritual identity of Muslims in Indonesia